A β-solidifying TiAl alloy reinforced with ultra-fine Y-rich precipitates. (February 2021) - Gu, Xu; Jiang, Sida; Cao, Fuyang; Zhang, Guoqing; Yang, Dongye; Guo, Shu; Song, Heqian; Sun, Jianfei
Highlights: A β-solidifying TiAl alloy reinforced with ultra-fine yttrium-rich precipitates was consolidated by spark plasma sintering. This TiAl alloy with refined duplex microstructure exhibited excellent tensile properties at room temperature. Two types of yttrium-rich precipitates were detected, and the crystallographic relationship between them and γ-TiAl matrix were determined. Abstract: A β-solidifying TiAl alloy with a refined microstructure and ultra-fine yttrium-rich precipitates that was consolidated by spark plasma sintering was investigated by scanning and transmission electron microscopies. Two categories of yttrium-rich precipitates, Y2 O3 and YAl2, with sizes ranging from tens to hundreds of nanometers were found to be dispersed within the matrix uniformly. The crystallographic relationship between the two precipitates and the γ-TiAl matrix was determined by the selected area electron diffraction and high-resolution transmission electron microscopy. This spark plasma sintered TiAl alloy was characterized by a uniform duplex microstructure, and it exhibited excellent tensile properties at room temperature. Typically, specimen sintered at 1150°C has an ultimate tensile strength of 1113.1 MPa, yield strength of 881MPa, and a moderate plastic elongation of 1.41%. Graphical Abstract: Image, graphical abstract